2007
DOI: 10.1161/hypertensionaha.107.089631
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinases in Early Hypertensive Vascular Remodeling

Abstract: Abstract-Hypertension is associated with vascular remodeling characterized by rearrangement of extracellular matrix proteins. To evaluate how matrix metalloproteinase (MMP)-9 contributes to the progression of hypertensive vascular disease in vivo, wild-type (wt) or MMP-9 Ϫ/Ϫ mice were treated with angiotensin II (Ang II; 1 g/kg per minute, by minipump) plus a 5% NaCl diet during 10 days. Baseline blood pressure was equivalent in wt and knockout mice, but Ang II treatment increased systolic blood pressure to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 29 publications
8
99
0
9
Order By: Relevance
“…MMPs (matrix metalloproteinases), especially MMP-9, seem to play a key role in vascular remodelling from the early stages of hypertensive damage, influencing also atherosclerotic lesion progression and plaque instability by their observed action against the stability of the plaque and the integrity of fibrous cap: MMPs, infact, can digest the fibrous cap and thereby participate in the triggering of plaque rupture [58]. In Ang II-induced hypertension, there is increased MMP-9 activity in conduit vessels.…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs (matrix metalloproteinases), especially MMP-9, seem to play a key role in vascular remodelling from the early stages of hypertensive damage, influencing also atherosclerotic lesion progression and plaque instability by their observed action against the stability of the plaque and the integrity of fibrous cap: MMPs, infact, can digest the fibrous cap and thereby participate in the triggering of plaque rupture [58]. In Ang II-induced hypertension, there is increased MMP-9 activity in conduit vessels.…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
“…In Ang II-induced hypertension, there is increased MMP-9 activity in conduit vessels. It has been observed that the absence of MMP-9 activity results in vessel stiffness, and MMP-9 activation is associated with a beneficial role early in hypertension [58].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
“…Studies (5,9,13,29,46) have shown that ANG II induces cardiac remodeling through an upregulation of MMP activity. We examined the expression of MMPs in cardiac tissue by real-time PCR and evaluated MMP activity by zymography.…”
Section: Cardiac Expression and Activity Of Mmpsmentioning
confidence: 99%
“…1,2 Pathological edema is a frequent complication. Hypertension is associated with extensive vascular remodeling characterized by rearrangement of extracellular matrix proteins [3][4][5] ; however, how this process occurs is not fully understood.…”
mentioning
confidence: 99%